The effect of food label literacy education on high school students’ knowledge - Debby Endayani Safitri; Nur Setiawati Rahayu (UHAMKA PRESS, 2018)
Nutrition fact is one of the packaged food label components that can show the nutritional content of food. The ability to read food labels is expected to increase the awareness of school children about the nutritional content of packaged foods so that students become more selective in choosing food and drinks. This study aimed at measuring the changing in the student’s nutrition knowledge after given the intervention. This study used pre-experimental design (one-group pretest-posttest design) held in June 2018. Subjects were 159 students of 7th and 8th grade of Teratai Putih Global Islamic High School. Data was tested by paired t-test to know the difference of subject’s knowledge after and before intervention. The subject’s scores were improving from 1.03 to 2.11. There was difference of knowledge between pre and post intervention (p<0,01).